Hubungan Lama Sakit dengan Status Gizi Anak Penderita Talasemia di RSUD Dr. Moewardi - Anisa, Ilma; Riza, Muhammad; Moelyo, Annang Giri (Nexus Kedokteran Klinik, 2013)
Background: Systemic complications that occur in children with thalassemia like hepatomegaly, hemosiderosis, bone deformities can affect nutrition disorder and growth retardation. The longer someone has suffered thalassemia, the more likely for the systemic disorder occurred. The aims of this study to find out the correlation between duration of illness with nutritional status of children with thalassemia in Dr. Moewardi Hospital. Methods: This is an observational analytic study using cross sectional design which was conducted from April to May 2013. Thirty children with thalassemia in the Dr. Moewardi Hospital were fulfill the restriction criteria. The duration of illness was acquired from medical record, while the nutritional status was obtained through measurements of weight, height, and the mid-upper arm circumference. The correlation between the duration of illness, gender, blood transfusion, iron chelating agents, splenomegaly, and 1 day food recall with nutritional status was analyzed by using Spearman test followed by the multivariate logistic regression analysis. Results: Spearman test analysis showed no significant correlation between duration of illness with nutritional status in children with thalassemia according to the weight/age and height/age indicator (p = 0,403 and p = 0,408). From the result of analysis on correlation between gender, blood transfusion, iron chelating agents, splenomegaly, and 1 day food recall with nutritional status according to the weight/age and height/age indicator (p > 0,05). Conclusions: There is no significant correlation between the duration of illness with the nutritional status of children with thalassemia according to the weight/age and height/age indicator in Dr. Moewardi Hospital. There is no correlation between gender, blood transfusion, iron chelating agents, splenomegaly, and 1 day food recall with nutritional status. Keywords: Duration of Illness, Nutritional Status, ThalassemiaÂ